ANALISIS PRODUKSI USAHA TANI TOMAT DI DESA LERO KECAMATAN SINDUE KABUPATEN DONGGALA - Fadli Fadli (Universitas Tadulako, 2022)
Indonesian agriculture is tropical agriculture because most of its areas are in the tropics which are derectly affected by the equator, which cust indonesian almost to two. Its agricultural business pattern is dominated by people’s agriculture which has an average area of ownership and managgement of its narrow and scattered land, in addition to being weak in capital ownership and less able to access capital resources in existing financial institution, especially in both government and private banking, this study aims to find out the influence of land area, seeds, fertilizer, labor on corn farming business in lero village, sindue district, Donggala regency. Released in November 2019 until January 2020. The result of t-test analysis show that partially affected land area is very real with t-count> t-table (3,353> 2,059) at a level. 5%, seeds significantly affected by t-count>t-table (4,152> 2,059) at a level 5% fertillizer significantly affected by t-count> t-table (3,894> 2,059) at the a level. 5% and significantly affected workforce with tcount>t-table (2,204> 2,059) at a lavel.5% simultaneously the results of F-test analysis showed that land area factors (XI), seeds (X2),fertilyzer (X3), and labor (X4) had a very significant effect on tomato prodution with F-count> F-tabl (50,168> 2,059).